Optimizing Islamic Boarding School Edupreneurship Through Internet of Things Adoption and Fuzzy Analytical Hierarchy Process - Lutfiyah, Konita; Maarif, Mohammad Syamsul; Asnawi, Yudha Heryawan; Arsyianti, Laily Dwi (Pandawan, 2025)
Islamic boarding schools are the oldest Islamic educational institutions that are deeply rooted in the history of the Indonesian nation. Since the 15th century, Islamic boarding schools have existed as a manifestation of the synergistic encounter between universal Islamic teachings and local wisdom. Islamic boarding schools can survive across time and generations, because the Islamic boarding school education system prioritizes the formation of spirituality, morality, noble morals and manners. The current study attempts to recommend a priority strategic in adopting Internet of Things (IoT) to create innovative services in islamic boarding School. The processing technique used to determine the strategy is the fuzzy Analytical Hierarchy Process (AHP). This research was conducted in Islamic Boarding School by Focus Group Discussion (FGD) with several experts. The expert is mayor of Depok, head of the Data and Information Center of the Ministry of Education and Culture, Director of Education Diniyah Islamic Boarding School, founder of Islamic boarding school Cendekia Amanah, Professor of Ushuluddin Faculty, IoT practitioner, alumni, and Islamic boarding school practitioner. The results show that the most dominant factor in improving services is human resources, and the actor is the islamic boarding management leader. The following finding is that the Increase organizational impact through service effectiveness and efficiency. The prior alternative strategy to recommend is by Building a technology culture among Islamic boarding school residents through Islamic boarding school values, habits and systems. The results of this study are presented and discussed, and the results of this study can be helpful for islamic boarding school in similar developing countries.